Correction: Ahmed et al. A Robust Deep Feature Extraction Method for Human Activity Recognition Using a Wavelet Based Spectral Visualisation Technique. Sensors 2024, 24, 4343 - Nadeem Ahmed; Md Obaydullah Al Numan; Raihan Kabir; Md Rashedul Islam; Yutaka Watanobe (Sensors, 2025)
There was an error in the original publication [...]